Systematic analysis of rice (Oryza sativa) metabolic responses to herbivory. (14th November 2015) - Alamgir, Kabir Md; Hojo, Yuko; Christeller, John T.; Fukumoto, Kaori; Isshiki, Ryutaro; Shinya, Tomonori; Baldwin, Ian T.; Galis, Ivan
Abstract: Plants defend against attack from herbivores by direct and indirect defence mechanisms mediated by the accumulation of phytoalexins and release of volatile signals, respectively. While the defensive arsenals of some plants, such as tobacco and Arabidopsis are well known, most of rice's ( Oryza sativa ) defence metabolites and their effectiveness against herbivores remain uncharacterized. Here, we used a non‐biassed metabolomics approach to identify many novel herbivory‐regulated metabolic signatures in rice. Most were up‐regulated by herbivore attack while only a few were suppressed. Two of the most prominent up‐regulated signatures were characterized as phenolamides (PAs), p‐ coumaroylputrescine and feruloylputrescine. PAs accumulated in response to attack by both chewing insects, i.e. feeding of the lawn armyworm ( Spodoptera mauritia ) and the rice skipper ( Parnara guttata ) larvae, and the attack of the sucking insect, the brown planthopper ( Nilaparvata lugens, BPH). In bioassays, BPH insects feeding on 15% sugar solution containing p‐ coumaroylputrescine or feruloylputrescine, at concentrations similar to those elicited by heavy BPH attack in rice, had a higher mortality compared to those feeding on sugar diet alone. Our results highlight PAs as a rapidly expanding new group of plant defence metabolites that are elicited by herbivore attack, and deter herbivores in rice and other plants. Abstract : We show that insect herbivory induces profound metabolic changes in rice plants. In particular, two metabolites, p ‐coumaroylputrescine and feruloylputrescine, consistently accumulated in rice leaves upon attack of various chewing and sucking insects. Amongst them, important rice pest the brown planthopper ( Nilaparvata lugens ) showed increased mortality when exposed to these metabolites added in the artificial diet during feeding.